'GIVE ACCORDING TO YOUR ABILITIES, RECEIVE ACCORDING TO YOUR NEEDS'. - Nov, Oded; Rao, Bharat (Communications of the ACM, 2008)
The article discusses the concept of "Give according to your abilities, receive according to your needs" (GARN) in computer programming. The authors detail the ways that software, hardware, computer networks, and online content all require mechanisms to prevent unauthorized use, the overuse of common resources, the use of resources without consent, and the blocking of resource access. Methods to identify and counter threats associated with the GARN phenomenon while developing computer software and infrastructure are included.